Personalization of loco-regional care for primary breast cancer patients (part 1). (May 2015) - Toi, Masakazu; Winer, Eric P; Benson, John R; Inamoto, Takashi; Forbes, John F; von Minckwitz, Gunter; Robertson, John FR; Grobmyer, Stephen R; Jatoi, Ismail; Sasano, Hironobu; Kunkler, Ian; Ho, Alice Y; et al.
ABSTRACT : Kyoto Breast Cancer Consensus Conference, Kyoto, Japan, 18–20 February 2014 The loco-regional management of breast cancer is increasingly complex with application of primary systemic therapies, oncoplastic techniques and genetic testing for breast cancer susceptibility. Personalization of loco-regional treatment is integral to optimization of breast cancer care. Clinical and pathological tumor stage, biological features and host factors influence loco-regional treatment strategies and extent of surgical procedures. Key issues including axillary staging, axillary treatment, radiation therapy, primary systemic therapy (PST), preoperative hormonal therapy and genetic predisposition were identified and discussed at the Kyoto Breast Cancer Consensus Conference (KBCCC2014). In the first of a two part conference scene, consensus recommendations for axillary management are presented and focus on the following topics: indications for completion axillary lymph node dissection in primary surgical patients with ≤2 macrometastases or any sentinel nodal deposits after PST; the timing of sentinel lymph node biopsy in the context of PST; use of axillary irradiation as a component of primary treatment plans and the role of intraoperative node assessment in the post-Z0011 era.